A gymnodont fish jaw with remarkable molariform teeth from the early Eocene of Gujarat, India (Teleostei, Tetraodontiformes). Issue 6 (2nd November 2017) - Bemis, Katherine E.; Tyler, James C.; Bemis, William E.; Kumar, Kishor; Rana, Rajendra Singh; Smith, Thierry
ABSTRACT: The lower jaw of a gymnodont fish collected from the lower Eocene Cambay Shale Formation in Gujarat Province, western India, has fused dentaries without a beak and a remarkable series of teeth that are unique among all known fossil and living Tetraodontiformes. The teeth are molariform, with raised spokes radiating inward from the emarginated peripheral edge of the crown. Tooth development is intraosseous, with new teeth developing in spongy bone before they erupt and attach to the dentary by pedicels. Although many of the 110 tooth loci in the fossil have lost their teeth, in life the teeth would have grown to fit tightly together to form a broad and continuous crushing surface. The estimated age of the Cambay Shale vertebrate fauna is ca. 54.5 Ma, making the jaw the second oldest confirmed gymnodont fossil. Preliminary comparisons with extant taxa of gymnodonts with fused dentaries (e.g., Diodon, Chilomycterus, and Mola ) show detailed similarities in jaw structure, but further study of the dentition is needed to better understand the evolutionary position of the new fossil. We describe the new gymnodont as † Avitoplectus molaris, gen. et sp. nov., in †Avitoplectidae, fam. nov., and place the family as incertae sedis within Gymnodontes. http://zoobank.org/urn:lsid:zoobank.org:pub:46BF7C65-2241-4B89-B088-6DC6721CD2FD Citation for this article: Bemis, K. E., J. C. Tyler, W. E. Bemis, K. Kumar, R. S. Rana, and T. Smith. 2017. A gymnodont fish jaw with remarkable molariform teeth from the early Eocene of Gujarat, India (Teleostei, Tetraodontiformes). Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1369422.